Development of TPS type cooperative learning tools integrated with huyula values in terms of the affective aspect - Modeong, Athir Mizhari; Odja, Abdul Haris; Buhungo, Trisnawaty Junus; Abdjul, Tirtawaty (Universitas Muhammadiyah Mataram, 2024)
This research aimed to produce a hight-quality cooperative learning tool with the Think Pair Share (TPS) model integrated with Huyula values, focusing on the affective aspect. This type of research falls under the Research and Development category, utilizing the ADDIE model. The research results indicated that: 1) the developed tool is valid and suitable, as evidenced by expert validation: 2) the developed tool is practical, demonstrated by successful implementation over three sessions with an average percentage of 96.30%, and a majority of students 96.28% responding positively.In conclusion, the cooperative learning tool using the Think Pair Share (TPS) model integrated with Huyula values, focusing on the affective aspect, meets the criteria for being valid and practical. So that, suitable for use.